FORMATION CONDITIONS AND CLASSIFICATION OF THE STRUCTURAL LANDSLIDES FOR THE LANDSLIDE HAZARD MODELLING - Shevchuk, V.; Ivanik, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Different classifications of the gravitational processes have been analyzed. It was proved that the structural landslides of the different rheological mechanism have a dominate role in the region with the complicated geological structure. New classification of the structural landslides with the determinative influence of destructive zones has been proposed. It is a base of the geological-physical models and a landslide hazard modeling.